1981
DOI: 10.1093/ajcn/34.7.1292
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status, globulin titers, and parasitic infections of two populations of Tanzanian school children

Abstract: Two schools in rural Tanzania were surveyed regarding the pupils' nutrition (weight and height), serum immunoglobulins (IgA, IgG, IgM, and IgE), autoantibodies, malaria antibodies, hepatitis B antigenemia, and fecal and urinary parasites. The survey attempted to quantify the relative importance of undernutrition and parasitic infestation in determining the serological abnormalities found. Of all the children surveyed 69% were undernourished (less than 80% of expected weight for age); 63% had fecal parasites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

1988
1988
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
0
14
0
4
Order By: Relevance
“…Some studies suggest a protective effect against malaria for wasted children [18] and children with stunting [19]. Other studies have found either no association between malnutrition and malaria [20-22] or even an increased risk of malaria among stunted [5,23] and underweight children [4]. In this population of very young HIV negative infants, no association between measures of malnutrition and malaria parasitaemia was observed.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies suggest a protective effect against malaria for wasted children [18] and children with stunting [19]. Other studies have found either no association between malnutrition and malaria [20-22] or even an increased risk of malaria among stunted [5,23] and underweight children [4]. In this population of very young HIV negative infants, no association between measures of malnutrition and malaria parasitaemia was observed.…”
Section: Discussionmentioning
confidence: 89%
“…This could be interpreted as a synergistic effect if malnutrition suppresses antibody response to malaria or possibly antagonistic if malnutrition protects against infection such that antibodies are not produced. In Tanzania, there was no effect of nutritional status on anti-parasite antibody levels [49]. A study in Burkina Faso found no association between parasite prevalence and nutritional status [50].…”
Section: Protein Energy Malnutrition (Pem)mentioning
confidence: 96%
“…7,8 However, this interaction between malnutrition and malaria is complex and varies depending on the definitions and indicators used for malnutrition measurements. [9][10][11] More specifically, the literature has supported that stunting (low height-forage), the indicator of chronic malnutrition, may increase the risk of malaria. 12 Whereas wasting (low weight-forheight), the indicator of acute malnutrition, appears to be associated with a decreased risk of malaria.…”
Section: Introductionmentioning
confidence: 99%